Women are Transmogrifying: History, Feminism and Australian Museums, 1975–2001. Issue 2 (2nd April 2016) - Paul, Mandy
ABSTRACT: 1975 was United Nations International Women's Year. It was also the year of the Pigott Report, Museums in Australia . This report identified and encouraged the rise of history and its move into museums, which was then facilitated by state sesquicentennials and the Bicentennial of 1988. The period between 1975 and the opening of the National Museum of Australia in 2001 saw a major shift in the place of history in the public culture of Australia. This article traces the relationship between the rise of history, more specifically social history, in museums and the impact of feminism and feminists on those cultural institutions. It documents a period of activism and change, as debate raged about whose history was represented in exhibitions and collections and the field was transformed by the entry of professional history curators. The late 1980s and first half of the 1990s appear to have been a high point of public discourse about women, history and representation within the museum sector. However, feminism and feminists have had a significant impact on the practice of social history curatorship in Australia, and, in turn, on Australian public culture.